2016
DOI: 10.1088/0957-4484/27/49/495604
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Ti–Ta thin films synthesized by combinatorial glancing angle sputter deposition

Abstract: Ti-Ta alloys are attractive materials for applications in actuators as well as biomedical implants. When fabricated as thin films, these alloys can potentially be employed as microactuators, components for micro-implantable devices and coatings on surgical implants. In this study, Ti Ta (x = 21, 30) nanocolumnar thin films are fabricated by glancing angle deposition (GLAD) at room temperature using TiTa and Ta sputter targets. Crystal structure, morphology and microstructure of the nanostructured thin films ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…The cross sections and surface morphology of the coatings deposited on Si substrates are presented in Figure and, respectively. A typical close‐packed columnar growth (Figure ) can be observed for all the films independently of the Ta content . It is interesting to note that the images show a dimple‐like structure indicative of the ductile fracture mechanism of the metallic coatings, very different to that observed for ceramic coatings.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…The cross sections and surface morphology of the coatings deposited on Si substrates are presented in Figure and, respectively. A typical close‐packed columnar growth (Figure ) can be observed for all the films independently of the Ta content . It is interesting to note that the images show a dimple‐like structure indicative of the ductile fracture mechanism of the metallic coatings, very different to that observed for ceramic coatings.…”
Section: Resultsmentioning
confidence: 81%
“…Motemani et al did also observed the formation of the metastable α̋ martensite phase in the as‐deposited coatings for Ta contents between 30 and 33 at%. The phase diagrams of metastable phases for the Ti‐Ta system indicates that the martensitic transformation ( M s ) temperature decreases as a function of the concentration of the β stabilizer .…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The literature proposes various approaches to fabricate combinatorial coatings, most of them being suitable only to a limited class of compounds. Among these, we can mention several physicalchemical deposition methods such as magnetron co-sputtering deposition [141], glancing angle deposition [142], co-electrodeposition [143], casting processes [144], or flow-coating methods [145]. An advanced experimental design could be envisioned in order to generate multi-compositional diagram 2D maps on high surface areas.…”
Section: Combinatorial Laser Technologiesmentioning
confidence: 99%